Promises and opportunity cost - Sengupta, Arjun; Vanberg, Christoph (Discussion paper series, 2020)
This paper experimentally investigates the hypothesis that promise-keeping behavior is affected by the opportunities that a counterpart foregoes by relying on the promise. We present two motivational mechanisms that could drive such an effect. One is that people dislike causing harm through a promise, and the natural way to measure such harm is to take into account what the counterpart would have received had she not relied on the promise. The other is that people may dislike causing regret in another person. We test these ideas in the context of an experimental trust game. The main treatment variable is the payoff that the first mover forgoes if he “trusts”. Consistent with our main hypothesis, we find that an increase in this foregone payoff increases promise-keeping behavior. The experiment is designed to rule out alternative explanations for such an effect. Our evidence suggests that the mechanism driving the effect may involve an aversion to causing regret in others.
Keywords: Graue Literatur